2020
DOI: 10.4252/wjsc.v12.i7.676
|View full text |Cite
|
Sign up to set email alerts
|

Application and prospect of adipose stem cell transplantation in treating lymphedema

Abstract: BACKGROUND Lymphedema is a chronic, debilitating and incurable disease that affects 0.13%-2% of the global population. Emerging evidence indicates that adipose-derived stem cells (ADSCs) might serve as suitable seed cells for lymphatic tissue engineering and lymphedema therapy. AIM To summarize applications of ADSCs for treating lymphedema in both animal studies and clinical trials. METHODS A systematic search was performed on four databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Increasing evidence indicates that there is an intrinsic correlation between adipose tissue and the lymphatic system. According to previous studies ( Takeda et al, 2015 ; Li et al, 2020 ), adipose-derived stem cells (ADSCs) could promote proliferation, migration, and tube formation of LECs in vitro by secreting various lymphangiogenic factors. In addition, it has been demonstrated that ADSCs can increase the number of lymphatic vessels and promote the restoration of lymphatic drainage in vivo ( Hayashida et al, 2017 ; Hu and Pan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that there is an intrinsic correlation between adipose tissue and the lymphatic system. According to previous studies ( Takeda et al, 2015 ; Li et al, 2020 ), adipose-derived stem cells (ADSCs) could promote proliferation, migration, and tube formation of LECs in vitro by secreting various lymphangiogenic factors. In addition, it has been demonstrated that ADSCs can increase the number of lymphatic vessels and promote the restoration of lymphatic drainage in vivo ( Hayashida et al, 2017 ; Hu and Pan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that cell therapy proved to generate a robust beneficial effect in animal models of secondary lymphedema. Although several in vitro and in vivo studies have reported beneficial effects of cell therapy against secondary lymphedema [ 21 , 49 , 50 ], a formal meta-analysis that assesses the regenerative activity of cell therapy in animal models of secondary lymphedema had not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, the safety of the combination of lymph node metastasis and adenoviral VEGF-C was demonstrated in a small trial of lymphedema associated with breast cancer (62). Danish research groups pioneered clinical trials of adipose-derived regenerative cells for lymphedema, and in 2016, Toyotaserkani et al reported a pilot study using adipose stem cells adjuvant fat transfer for lymphedema, where 4 weeks after treatment, patients' daily arm heaviness, tension symptoms were significantly reduced, the number of compression treatments was decreased, the volume of the affected limb was reduced, and no postoperative complications or adverse events occurred; and they were conducting a phase III clinical trial (63,64). As discussed above, a better understanding of how different genes or molecules affect the normal function of the lymphatic vascular system and the identification of new pro-lymphopoietic factors will help in the diagnosis and eventual treatment of patients with symptomatic or asymptomatic lymphatic disorders and related comorbidities.…”
Section: Cluster 2: the Lymphatic-vessel-related Research 4321 Lympha...mentioning
confidence: 99%